Appropriation in a World Heritage Site: Mozambique Island's visible and invisible complexities - Dantas e Sa, Vanessa Ulia (My University, 2010)
Abstract: Mozambique Island, situated in the North of Mozambique, was declared a World Heritage Site by UNESCO in 1991, for its unique architecture, a testimony to the amalgamation of different cultural and scientific practices from the 16th century onwards. Generally this research is about a paradox: Mozambique Island has been recognised as a special place, and yet it is in a state of disrepair and buildings are being rebuilt and reconstructed in ways that are not consistent with the designation. Situated within the field of Human Geography, my research question Why is the World Heritage of Mozambique Island in its present state is answered through an exploration of the concept of appropriation and the importance of recognising the invisible and visible complexities of a locality. I argue that the complexities of Mozambique Island (viewed from differing scales) determine the perception of the islanders have of how World Heritage could potentially benefit them, which in turn, directly informs conservation, maintenance and management strategies (at community, city council, regional and national levels). The appropriation of identity and space only happens when the individual or group concerned think that they would benefit at some level from it. In the case of Mozambique Island, most subjects interviewed do not know what World Heritage is, how they could benefit from potential tourism associated with it and therefore why they should be putting extra effort into conserving it. Through a conversation between issues of World Heritage, identity, space, ownership, tourism and scale, I propose that in Mozambique Island there is a case of nonappropriation of its World Heritage due to its complexities, the main being: severe poverty, lack of education, bad governance, a culture of dependency and poor support from the national and regional government and UNESCO.